2011
DOI: 10.1080/02701960.2011.572034
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Willingness to Evacuate Among Older Adults

Abstract: The issues of rising numbers of disasters, overwhelming increases in number of older adults, and historically flawed evacuations present real challenges. During the next two decades, the number of American baby boomers, who turn 65, will increase by 40%. As evidenced by recent disasters, the imperfections and vulnerabilities of flawed evacuations for older adults are still present. This study examined the level of willingness to evacuate among older adults in the event of a disaster. Despite the extensive lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…46 The US population continues to age 47 and during the next 2 decades, the number of American baby boomers who turn 65 will increase by 40%. 48 The elderly and those with medical needs, although often the most vulnerable to the immediate-and longer-term • Home Medical Equipment and Propensity to Evacuate by Household Composition q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q • Mobility, Sensory, and Cognitive Limitations and Propensity to Evacuate by Household Composition q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q health impacts of a severe storm event, typically have a lower preparedness relative other groups. 49,50 As these parsimonious descriptive statistics show, the presence of chronic conditions; ADL dependence; electric medical equipment; and mobility, cognitive, and sensory impairment are only on occasion modestly associated with household evacuation.…”
Section: • Implications and Conclusionmentioning
confidence: 99%
“…46 The US population continues to age 47 and during the next 2 decades, the number of American baby boomers who turn 65 will increase by 40%. 48 The elderly and those with medical needs, although often the most vulnerable to the immediate-and longer-term • Home Medical Equipment and Propensity to Evacuate by Household Composition q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q • Mobility, Sensory, and Cognitive Limitations and Propensity to Evacuate by Household Composition q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q health impacts of a severe storm event, typically have a lower preparedness relative other groups. 49,50 As these parsimonious descriptive statistics show, the presence of chronic conditions; ADL dependence; electric medical equipment; and mobility, cognitive, and sensory impairment are only on occasion modestly associated with household evacuation.…”
Section: • Implications and Conclusionmentioning
confidence: 99%
“…ans ou plus vivant dans un quartier défavorisé où les infrastructures sont plus ou moins solides sont plus susceptibles d'être touchées par les catastrophes et de développer divers problèmes de santé physiques et psychologiques (Kamo et al, 2011;Gray-Graves, Turner, & Swam, 2011;Thomas & Durant, 2011;Zakour & Harrel, 2003 (Aldrich & Benson, 2008;HelpAge International, 1999;Thomas & Durant, 2011). La vulnérabilité des personnes âgées de 65 ans ou plus semble trop souvent ignorée par les autorités gouvernementales et civiles, même si des organismes évaluent les besoins des victimes afin de déterminer Tordre des priorités de la communauté (Aldrich & Benson, 2008;HelpAge International, 1999 (Bolin & Klenow, 1988).…”
Section: Les Facteurs Qui Vulnérabilisent Ou Qui Protègent Les Personunclassified
“…24 Other studies have found that the intention to evacuate changes, depending on the vulnerable populations. 9,[25][26][27][28][29][30] Studies examining barriers to evacuation, which help explain the difference between intention to evacuate and actual evacuation, have also been conducted, with particular emphasis on vulnerable populations. [31][32][33][34] Income level has been shown to affect decisions regarding evacuation.…”
Section: Introductionmentioning
confidence: 99%